Butterflies (Lepidoptera Papilionoidea) diversity at Endau-Rompin Johor national park, Malaysia and prioritising the potential groups for nature tourism product - Ismail, Norradihah; Mohamed, Maryati; Mohd Salleh, Kahirol; Chooi, Khim Phon; Tokiman, Lili (Department of Wildlife and National Parks (PERHILITAN), 2018)
From a total of 17,461 species of butterfly described worldwide, at least twothird are from the tropics. Peninsular Malaysia is home to 1038 butterfly species. Endau-Rompin Johor National Park (ERJNP) in particular recorded 349 species as analysed from collections of 1987 to 2015. It represents 34% of butterfly fauna in Peninsular Malaysia. This paper aims (i) to document the diversity of butterfly in ERJNP and (ii) identify potential groups of butterfly that satisfy six criteria for good nature tourism product. The criteria are reliability of sighting, safe, with unique morphology and behaviour, rare or endemic and with cultural linkage. The samplings were done manually using aerial net and trapping using fruit baits along two 1 km transects in the eastern part of ERJNP (Nature Education and Research Centre and Kuala Jasin) from February 2014 to July 2015. This study successfully recorded 131 species comprising of 491 individuals from five families. Nymphalidae was the most dominant family, making up 51% of butterfly abundance and richness. Five dominant species were recorded with 31 to 43 individuals per species. The values of Shannon diversity index (H’) and species evenness index (E’) were 4.123 and 0.471 respectively. Significantly, eight species collected were protected under the Wildlife Conservation Act, 2010 and 14 were considered rare and uncommon. Butterflies are frequently encountered, morphologically and behaviourally unique. These attributes fascinate visitors of the park, thus butterfly has a potential to be promoted as new attraction for nature tourism in ERJNP.